RNA-Binding Proteins in the Post-transcriptional Control of Skeletal Muscle Development, Regeneration and Disease - Shi, De-Li; Grifone, Raphaëlle (Frontiers in Cell and Developmental Biology, 2021)
Embryonic myogenesis is a temporally and spatially regulated process that leads to the formation of skeletal muscular tissue. Mononucleated myoblasts derived from myogenic progenitor cells within the somites undergo proliferation, migration and differentiation to elongate and fuse into multinucleated functional myofibers. Skeletal muscle is the most abundant tissue of the body and has the remarkable ability to self-repair by re-activating the myogenic program in muscle stem cells or satellite cells. Post-transcriptional regulation of gene expression mediated by RNA-binding proteins is critically required for muscle development during embryogenesis and for muscle homeostasis in the adult. Differential subcellular localization and activity of RNA-binding proteins orchestrates target gene expression at multiple levels to regulate different steps of myogenesis. Dysfunctions of these post-transcriptional regulators are closely associated with defects in muscle development and homeostasis, resulting in muscle degeneration and neuromuscular disease. RNA-binding proteins display both overlapping and distinct targets in muscle cells. Thus they function either cooperatively or antagonistically to coordinate myoblast proliferation and differentiation. The dynamic interplay of their regulatory activity controls the progression of myogenic program as well as stem cell quiescence and activation. Here we review past achievements and recent advances in understanding the functions of RNA-binding proteins during skeletal muscle development, regeneration and disease, with the aim to identify fundamental questions still open for further investigations.